A Critical Interpretation on Sickle Cell Anaemia: A Genetic Disorder A Brief Review Study - Chandeshwar, Sonal; Khichariya, S D; Baghel, Pramod Kumar (International Research Journal of Ayurveda & Yoga, 2021)
HbS is a homozygous type of Sickle Cell Anaemia (HbSS). This is the product of a single point substitution of β-globin chain valine for glutamine 6. This limits the solubility of the red cells, which in turn leads to the polymerization and vaso-occlusion of the vasculature. The gene for β-globin is found in the short arm of chromosome 11. The combination of two β-globin mutant subunits forms haemoglobin S (HbS). Under low oxygen conditions, the absence of polar amino acid at the six-point position of the β-globin chain promotes non covalent hemoglobin polymerization, which distorts the composition of red blood cells in the sickle and decreases their elasticity. Low oxygen tension in sickle cell disease promotes the sickling of red blood cells and frequent episodes of sickling weaken the cell membrane and reduces the elasticity of the cell. When normal oxygen voltage is restored, these cells fail to return to normal form. As a result, these compact blood cells cannot deform as they travel through small capillaries, leading to occlusion of the arteries and Ischemia. The underlying condition anaemia is caused by hemolysis, the breakdown of the red cells within the spleen.